(untitled) (Universal International Scientific Journal, 2026)
The article is devoted to the study of socio-psychological methods of developing memory in children of primary school age. Based on modern pedagogical and psychological research, the formation of children’s memory through the social environment, the influence of teachers and parents, as well as group activities, is analyzed. This article shows ways to strengthen memory in young children through effective memory exercises, games and interactive methods. Also, practical recommendations are given based on the theories of Vygotsky, Piaget, Bruner and other psychologists